2005
DOI: 10.1021/bi050643x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Neurotrophic Action of Nobiletin in PC12D Cells

Abstract: Nobiletin is a nonpeptide compound with a low molecular weight from a citrus fruit and has the activity to rescue bulbectomy-induced memory impairment. Here we describe that nobiletin itself induces neurite outgrowth in PC12D cells, a rat pheochromocytoma cell line, like NGF, and the molecular mechanism of its neurotrophic action. As cultured in the presence of nobiletin or NGF for 48 h and then assayed using a scanning electron microscope, PC12D cells treated with nobiletin showed morphology with flatter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 37 publications
1
99
0
Order By: Relevance
“…10) We reported previously that CRE-dependent transcription was enhanced by nobiletin by activation of the PKA/MEK/ERK/ CREB signal pathway in PC12D cells. 15,20) Moreover, our previous report showed that nobiletin ameliorates the NMDA receptor antagonist-induced learning impairment in association with ERK activation in mice. 18) This is the first report demonstrating that nobiletin significantly upregulated NR1, NR2A, and NR2B mRNA levels in PC12D cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…10) We reported previously that CRE-dependent transcription was enhanced by nobiletin by activation of the PKA/MEK/ERK/ CREB signal pathway in PC12D cells. 15,20) Moreover, our previous report showed that nobiletin ameliorates the NMDA receptor antagonist-induced learning impairment in association with ERK activation in mice. 18) This is the first report demonstrating that nobiletin significantly upregulated NR1, NR2A, and NR2B mRNA levels in PC12D cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…19) Nobiletin prominently stimulates CRE-dependent transcription in PC12D cells 20) by activating the PKA/MEK/extracellular signal-regulated kinase (ERK)/CREB signaling pathway. 15) We further revealed that nobiletin restores the CREB phosphorylation suppressed by Aβ peptides in hippocampal neurons. 17) However, it remains unclear whether the genes involved in learning and memory are modulated by nobiletin.…”
mentioning
confidence: 76%
See 3 more Smart Citations